Optimizing Therapy for Acute Coronary Syndrome - Rizzo, Toni (MD Conference Express, 2015)
Percutaneous coronary intervention is the primary treatment for patients with acute coronary syndrome. Selective use of manual thrombectomy may be an effective option. P2Y12 inhibitors are a treatment of choice in patients with STEMI. Bivalirudin reduces adverse cardiac events and is associated with reduced bleeding. When percutaneous coronary intervention is delayed in patients with STEMI, fibrinolytic therapy should be administered.